Advances toward LSD1 inhibitors for cancer therapy. (July 2017) - Fu, Xiaoli; Zhang, Peng; Yu, Bin
LSD1 has become an important biologically validated epigenetic target for cancer therapy since its identification in 2004. LSD1 mediates many cellular signaling pathways and is involved in the initiation and development of cancers. Aberrant overexpression of LSD1 has been observed in different types of cancers, and inactivation by small molecules suppresses cancer cell differentiation, proliferation, invasion and migration. To date, a large number of LSD1 inhibitors have been reported, RG6016, GSK-2879552, INCB059872, IMG-7289 and CC-90011 are currently undergoing clinical assessment for the treatment of acute myeloid leukemia, small-cell lung cancer, etc. In this review, we briefly highlight recent advances of LSD1 inhibitors mainly covering the literatures from 2015 to 2017 and tentatively propose our perspectives on the design of new LSD1 inhibitors for cancer therapy.